2015
DOI: 10.1038/srep18583
|View full text |Cite
|
Sign up to set email alerts
|

From red to green: the propidium iodide-permeable membrane of Shewanella decolorationis S12 is repairable

Abstract: Viability is a common issue of concern in almost all microbial processes. Fluorescence-based assays are extensively used in microbial viability assessment, especially for mixed-species samples or biofilms. Propidium iodide (PI) is the most frequently used fluorescence indicator for cell viability based on the membrane permeability. Our results showed that the accumulation of succinate from fumarate respiration could induce PI-permeability in Shewanella decolorationis biofilm cells. Confocal laser scanning micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 20 publications
2
38
0
Order By: Relevance
“…Other dyes such as Sytox Green or PI can be used to establish whether HDPs damage cytoplasmic membranes and interact with intracellular nucleic acids (Sträuber and Müller, 2010;Davey and Hexley, 2011;Wenzel et al, 2015;Yang Y. et al, 2015;Pulido et al, 2016;Yasir et al, 2019). These dyes penetrate through membranes in which pores are present and can be used to probe differences in pore size and structure.…”
Section: Cytoplasmic Membrane Disruptionmentioning
confidence: 99%
“…Other dyes such as Sytox Green or PI can be used to establish whether HDPs damage cytoplasmic membranes and interact with intracellular nucleic acids (Sträuber and Müller, 2010;Davey and Hexley, 2011;Wenzel et al, 2015;Yang Y. et al, 2015;Pulido et al, 2016;Yasir et al, 2019). These dyes penetrate through membranes in which pores are present and can be used to probe differences in pore size and structure.…”
Section: Cytoplasmic Membrane Disruptionmentioning
confidence: 99%
“…However, PI uptake is actually dependent on the physiological state of the bacterial cells (Shi et al, 2007), and a recent study (Kirchhoff and Cypionka, 2017) found that the membrane potential of cells could also affect the uptake of PI in viable cells, which would lead to the erroneous conclusion that PI-stained cells were dead. It has also been reported that the accumulation of succinate from fumarate respiration could induce PI permeability in Shewanella decolorationis biofilm cells, and the PI-permeable membrane could be repaired in situ when the extracellular succinate was eliminated by switching fumarate respiration to electrode respiration (Yang et al, 2015). To eliminate possible errors, the cell membrane potential of K. xylinus strains and the uptake of PI in viable cells requires further investigation.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous reports 47,48,49 has been using Propidium iodide (PI) to characterize the dead or nonviable cells from living prokaryotic cells, as PI only stain cells with irreparably damaged membranes that can be described as nonviable or dead. The results of this study showed an increase of bacteria stained with PI after 1hour penicillin treatment and also after aPDT.…”
Section: -Discussionmentioning
confidence: 99%